Responsibility or Responsibilization in Medical Evidencing of Domestic Violence? The Belgian Case Analyzed Through a Care Ethical Lens - Vergaert, Eva (Violence against women, 2024)
The prosecution of domestic violence remains a complex process within criminal policy in Belgium. Evidence is often reliant on medical certificates or injury reports, necessary for victims who want to file official complaints. However, medical evidencing is a contentious issue. Based on qualitative research among public prosecutors, victims, and general practitioners in Belgium, this study analyses the challenges these groups face through an ethics of care lens. Despite their crucial importance in legal procedures, the use of certificates is surrounded by contradictions. The issues point to an unequal distribution of responsibilities, which masks institutional and political responsibilities and enhances the responsibilization of victims.